KREDIBILITAS PERIWAYAT MURJI’AH DALAM KITAB SAHIH AL-BUKHARI STUDI JARH WA TA’DIL TERHADAP IBRAHIM BIN TAHMAN - Hamzah, Hakma; Utama, Zoli (IAINU Kebumen Prodi IAT, 2025)
The early development of hadith studies was accompanied by the development of various Islamic ideologies that influenced the originality of the traditions themselves. In this context, followers of certain groups often falsified traditions due to their bigotry towards their group. They are referred to as innovators. Among the scholars of hadith criticism, the narration of the narrator of ahl bid'ah is accepted and rejected by some. One example is Ibrahim b. Tahman, who was affiliated with the Murji'ah group and whose hadith is recorded in Sahih al-Bukhari. This paper aims to prove the capacity of Ibrahim b. Tahman as a Murji'ah narrator whose narration is accepted by al-Bukhari. The research method used is library research with a qualitative approach, relying on sources from various literatures. The results showed that: (1) Ibrahim b. Tahman has a strong intellectual capacity in the field of hadith, as evidenced by the high praise given by scholars who observe hadith narrators. This indicates that he fulfills the criteria of al-Bukhari's rijalul hadith. (2) The traditions narrated by Ibrahim b. Tahman do not reflect his Murji'ah understanding. On the contrary he narrated the traditions in the same manner as other Sunni narrators showing integrity and authenticity in his narration.